EFEKTIVITAS STRATEGI PEMBELAJARAN BERBASIS PROYEK (PROJECT BASED LEARNING) TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA - Fitri, Ratna Property; Fitri Ningsih Oktavia Nababan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study focuses on examining the implementation of the Project-Based Learning strategy in improving students' critical thinking skills during the learning process. The problem underlying this research is related to the still limited ability of students to analyze critically, which is influenced by the tendency of teacher-centered learning and the lack of student engagement in learning. This study uses a qualitative approach with a library research method. The data sources were obtained through the exploration of various scientific literature, including journals, books, and other academic publications related to project-based learning and the development of critical thinking skills. The analysis was carried out descriptively by emphasizing the interpretation of relevant findings. The results of the study show that the use of Project-Based Learning provides a positive contribution in optimizing student engagement in learning. This strategy also directs students to examine problems more deeply, fosters independence, and enhances their ability to generate ideas. Additionally, students' critical thinking skills develop through activities that require discussion, exploration, and problem-solving related to real-life situations. Therefore, Project-Based Learning can be considered an adaptive and contextual learning approach in efforts to improve the quality of learning while strengthening students' critical thinking abilities.